Analisis Perbandingan Metode Pra Pemrosesan Citra untuk Deteksi Tepi Canny pada Citra Berbagai Kondisi Jalan menggunakan Bahasa Pemrograman Python - Wicaksono, Damar; Almeyda, Diva Putra; Putra, Irfan Mikola Muldiyanto; Malihatuningrum, Letty (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2024)
Edge detection is one of the essential techniques in digital image processing used to identify sudden changes in pixel intensity in an object. In the context of road marking detection on highways, accurate edge detection plays a crucial role in improving motorist safety and navigation. The Canny Edge Detection method has been proven effective in detecting edges with high accuracy in digital image processing. However, applying Canny Edge Detection on road images in various conditions still requires further research. This research aims to implement the Canny Edge Detection method in road marking detection on highway images. The main stages of this research include image pre-processing, where noise is removed, and the image is converted into a grayscale image to prepare the image before edge detection using the Canny method. In addition, a comparison will be made with several other image pre-processing methods, such as median and bilateral blur, to determine the most effective method for edge detection on road markings. Based on the research results, applying the Canny Edge Detection method with pre-processing using median blur is a practical approach to road marking detection on highway images. This method can produce accurate and optimized edge detection, which can be the basis for developing automatic road marking detection systems on highways. The findings can contribute to the improvement of motorist safety and navigation as well as the development of more accurate and effective edge detection technology on road markings.